Palaeobotanical study of Polichnitos region, southern part of Lesbos Island, Greece (preliminary results on angiosperm wood). - Mantzouka, D.; Sakala, J.; Kvaček, Z.; Karakitsios, V. (Bulletin of the Geological Society of Greece, 2013)
The present contribution brings new scientific data for the palaeoflora of Lesbos based on new collections of plant fossils which were discovered in 2011 at six new localities from the southern part of Lesbos Island. This study resumes the published data both on the palaeovegetation of the Petrified Forest and the palaeogeography of Lesbos Island during the Neogene. The new palaeobotanical study with more than seventy new samples of fossilized wood from the broader area of Polichnitos region gives new information about the palaeobotanical and palaeontological content of this area. It is reported for the first time here the existence of a diversified fossil wood assemblage from the southern part of the Island as long as the identification of three types of lauraceous wood according to their idioblasts characteristics.